Retrospective analysis of the pharmaceutical market of cardiological drugs in Ukraine for 2016-2020 - N. A. Symonenko; M. V. Podgaina; A. S. Nemchenko; O. S. Spychak (The State Expert Center of the Ministry of Health of Ukraine, 2021)
In Ukraine, cardiovascular disease is the leading cause of death and is the highest cause of death among all countries. Nationwide, cardiovascular disease's mortality has increased by almost 8% over the past 29 years. The aim of the work was to analyze the domestic pharmaceutical market of cardiac drugs (code of anatomical-therapeutic chemical classification (hereinafter - ATС) - C01, and C01 E separately) for the 2016-2020 in terms of pharmacotherapeutic groups, manufacturers, dosage forms and others. The object of the study was the data of the State Expert Center of the Ministry of Health of Ukraine, the proposals of distributors received from the «Morion» platform for 2016-2020. The research was carried out using modern methods of analysis, systematization and generalization, mathematical and statistical calculations. According to the database of the State Expert Center of the Ministry of Health in Ukraine, 256 cardiac drugs by dosage forms have been registered. Analysis of the group of cardiac drugs by ATС classification, allowed to establish a significant dominance of group C01 E - Other cardiac drugs - from 66% to 68% over the years of the study. According to the results of the analysis, a positive trend has been established - the dominance of domestically produced drugs in the group of cardiac drugs in the pharmaceutical market of Ukraine during 2016-2020. The general list of manufacturers presenting cardiac drugs in Ukraine consists of 66-68 companies, where the share of domestic companies was 53-55% during the study period. There is a steady trend towards a slight predominance of solid dosage forms (54-56% during the study period). In summary, it should be noted that the analysis of the domestic wholesale market of cardiac drugs showed a significant wide of the group's assortment, the significant dominance of the group «Other cardiac drugs» in the overall structure, showed a positive trend of domestic cardiac drugs; among dosage forms, solid and liquid dosage forms have been presented evenly.